APPLICATION OF CUBIT ESTIMATING PRO IN COST ESTIMATION FOR UNDERGRADUATE QUANTITY SURVEYORS: IMPLICATION FOR DEVELOPING COST ESTIMATION SKILLS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
In this research paper, we explore the utilization of Cubit Estimating PRO, a construction estimating and takeoff software, within the context of undergraduate quantity surveying education. The present study explored the role of Cubit Estimating Pro in cost estimation for undergraduate quantity surveyors at the National Institute of Construction Technology and Management, Uromi, Edo State, Nigeria. The results indicate that only 9% of respondents reported low competence. Approximately 27% of respondents demonstrated moderate competence. A significant majority (64%) exhibited high competence in utilizing Cubit Estimating PRO. These favorable outcomes suggest that the software positively contributes to developing cost estimation skills among quantity surveyors. By examining the practical application of Cubit Estimating PRO, the study aims to provide insights into how this tool enhances accuracy, efficiency, and proficiency in cost estimation.